A Novel DC-AC Inverter Topology to Eliminate Leakage Current - Tarek Selmi; Maher Rezgui (International Journal of Power Electronics and Drive Systems (IJPEDS), 2018)
Experiments confirmed that Transformerless Inverters (TIs) deliver more reliability and higher energy efficiency. Nonetheless, one of the shortcomings of TIs is the leakage current that occurs between the photovoltaic (PV) string terminals and the ground. Such a drawback is justified by the non-galvanic isolation caused by the transformer being omitted. As such, this study is intended to develop a novel TI inverter topology for solar PV systems. The latter is meant to remove the leakage current and enhance the operating system of the entire PV conversion as well. Added to its null zero-crossing distortion and capability regarding energy efficiency, the developed TI, being validated by simulation and experiment, eradicated the leakage current.